Sacubitril with valsartan, a modern pharmacotherapy in heart failure - a literature review - Bartosz Sadłowski; Paula Bieganek; Stanisław Łukaszewicz; Piotr Pawłowski; Julia Rybak; Jakub Kordialik; Julia Koćwin; Sandra Sarnacka; Michał Tokarski; Angelika Banasiak (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Heart failure is one of the most common cardiovascular diseases worldwide. It is an important factor leading to a reduced, health-related quality of life (HRQoL) not only because of its various symptoms but also due to loss of jobs or increase in medical expenses impairing the socioeconomic status of the sick. Nowadays scientists face this problem and are trying to invent specific pharmacotherapy that allows it to extend life and improve its quality. One of the elements of modern pharmacotherapy is the combination of sacubitril with valsartan. This work aims to evaluate the effect of this drug on the length and quality of life of patients with heart failure. Materials and methods: This article is a literature review based on publications from PubMed, Cochrane Library, ClinicalKey released since 2014, keywords included: sacubitril/valsartan; angiotensin receptor-neprilysin inhibitor; ARNI; heart failure. The state of knowledge: The use of sacubitril/valsartan drugs is an established agent used to reduce the risk of death from any cause in all patients with heart failure with reduced ejection fraction, death from cardiovascular causes and the rate of hospitalization due to exacerbation of symptoms. Some study analyses also indicate the utility of using sacubitril/valsartan in HFmrEF and HFpEF to reduce the rate of cardiovascular events and hospitalization because of heart failure. Conclusions: The use of sacubitril/valsartan is recognized to improve prognosis in patients with HFrEF. Evidence supporting its efficacy in the subgroup of patients with mid-range and preserved ejection fraction is still insufficient and requires further investigation.